Spatial and temporal aspects of slope hazards along a railroad corridor in the Canadian Cordillera - Macciotta, R; Cruden, DM; Martin, CD; Morgenstern, NR; Petrov, M (Slope 2013: 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
A successful slope management program depends on understanding the interaction between the potential slope failure and the elements at risk. This interaction defines the magnitude and likelihood of the potential consequences, which in turn defines the need for allocating resources for risk mitigation. The interaction can be divided into the probability of interaction between the displaced material and the elements at risk, and the degree of loss should impact occur. In this paper, the temporal and spatial aspects of landslides are analysed along a section of a railroad corridor through the Canadian Cordillera. The temporal and spatial aspects of the elements at risk are discussed and illustrated within the context of railroad freight train operations. An example is presented where the annual frequency of interaction between landslides and freight trains is estimated, and the associated spatial and temporal variability analysed. The paper highlights the importance, within a slope risk management strategy, of understanding landslide trends in space and time and how these spatial and temporal trends are related to morphology, geology and triggering mechanisms.